Recent Investigations into Pig Antigen and Anti-Pig Antibody Expression - Byrne, Guerard W. (Int J Surg, 2015)
Genetic engineering of donor pigs to eliminate expression of the dominant xenogeneic antigen galactose α1,3 galactose (Gal) has created a sea change in the immunobiology of xenograft rejection. Antibody mediated xenograft rejection of GGTA-1 α-galactosyltransferase (GTKO) deficient organs is now directed to a combination of non-Gal pig protein and carbohydrate antigens. Glycan analysis of GTKO tissues identified no new neo-antigens but detected high levels of N-acetylneuraminic acid (Neu5Gc) modified glycoproteins and glycolipids. Humans produce anti-Neu5Gc antibody and in very limited clinical studies sometimes show an induced anti-Neu5Gc antibody response after challenge with pig tissue. The pathogenicity of anti-Neu5Gc antibody in xenotransplantation is not clear however as non-human transplant models, critical for modelling anti-Gal immunity, do not produce anti-Neu5Gc antibody. Antibody induced after xenotransplantation in non-human primates is directed to an array of pig endothelial cells proteins and to a glycan produced by the pig B4GALNT2 gene. We anticipate that immune suppression will significantly affect the T-cell dependent and independent specificity of an induced antibody response and that donor pigs deficient in synthesis of multiple xenogeneic glycans will be important to future studies.